Bariatric Surgery and Non-Alcoholic Fatty Liver Disease: Current and Potential Future Treatments - Sasaki, Akira; Nitta, Hiroyuki; Otsuka, Koki; Umemura, Akira; Baba, Shigeaki; Obuchi, Toru; Wakabayashi, Go (Frontiers in Endocrinology, 2014)
Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) are increasingly common cause of chronic liver disease worldwide. The diagnosis of NASH is challenging as most affected patients are symptom-free and the role of routine screening is not clearly established. Most patients with severe obesity who undergo bariatric surgery have NAFLD, which is associated insulin resistance, type 2 diabetes mellitus (T2DM), hypertension, and obesity-related dyslipidemia. The effective treatment for NAFLD is weight reduction through lifestyle modifications, antiobesity medication, or bariatric surgery. Among these treatments, bariatric surgery is the most reliable method for achieving substantial, sustained weight loss. This procedure is safe when performed by a skilled surgeon, and the benefits include reduced weight, improved quality of life, decreased obesity-related comorbidities, and increased life expectancy. Further research is urgently needed to determine the best use of bariatric surgery with NAFLD patients at high risk of developing liver cirrhosis and its role in modulating complications of NAFLD, such as T2DM and cardiovascular disease. The current evidence suggests that bariatric surgery for patients with severe obesity decreases the grade of steatosis, hepatic inflammation, and fibrosis. However, further long-term studies are required to confirm the true effects before recommending bariatric surgery as a potential treatment for nonalcoholic steatohepatitis.